A Cu3P nanowire enabling high-efficiency, reliable, and energy-efficient low-voltage electroporation-inactivation of pathogens in water. Issue 39 (26th September 2018) - Huo, Zheng-Yang; Zhou, Jian-Feng; Wu, Yutong; Wu, Yin-Hu; Liu, Hai; Liu, Nian; Hu, Hong-Ying; Xie, Xing
Abstract : A Cu3 PNW–Cu electrode serves as an efficient and stable electrode for low-voltage electroporation-inactivation of pathogens in water with high energy efficiency. Abstract : Pathogen infection has become the major reason for human morbidity and mortality in the world. However, common bacterial inactivation methods ( e.g., chlorination, ultraviolet radiation, and ozonization) have significant drawbacks such as carcinogenic byproduct formation, energy intensiveness, and/or regrowth of pathogens. Nanowire-assisted low-voltage electroporation enables effective and energy-efficient bacterial inactivation. Here, we develop a new Cu3 P nanowire-assisted copper mesh (Cu3 PNW–Cu) electrode via an in situ growth followed by a phosphidation method and, for the first time, introduce the Cu3 PNWs in the water purification process. An electroporation-disinfection cell (EDC) equipped with two such electrodes achieves superior bacterial inactivation performance (>6.0 log removal; no live bacteria in the effluent) with a low voltage of 1 V and a high flux of 2.0 m 3 h −1 m −2 . Under such operating conditions, the Cu3 PNW–Cu electrode continuously treats water for 12 h while maintaining complete bacterial inactivation. The disinfection mechanism of electroporation guarantees an exceedingly low level of energy consumption: only 1.2 J for treating 1 L of water. To our knowledge, this is the lowest value obtained to date: >5 orders of magnitude lower than the typical energy consumption for bacterial inactivation using electroporation (150 kJ L −1 ).